Principles of radiographic positioning and procedures pocket guide - Greathouse, Joanne S.; Carlton, Richard R.; Adler, Arlene McKenna (Stamford, Conn. : Cengage Learning, 2015)
Includes quick reference sections for positioning procedures and radiation protection standards, descriptions of basic procedural details, typical technical considerations, and appropriate modifications for 165 common procedures.
Includes bibliographical references (p. 399) and index.
Keywords: Radiography, Medical -- Positioning; Radiography, Medical -- Positioning -- Handbooks, manuals, etc